IMPLEMENTASI KURIKULUM MERDEKA DALAM PENGEMBANGAN KARAKTER PESERTA DIDIK ABAD 21 - Aning Tri Diastutik; Sangkot Abdullah Efendi Harahap; Robiatul Adawiyah; M. Robby Salim; Siti julhijjah; Indrahambali (STKIP Subang, 2025)
ABSTRACT This article examines how the implementation of the Merdeka Curriculum contributes to the development of 21st-century student character through a literature review approach. The Merdeka Curriculum emphasizes student-centered learning, curricular flexibility, and character formation grounded in the Profile of Pancasila Students and project-based learning. In response to 21st-century demands, schools are expected to cultivate not only cognitive abilities but also socio-emotional skills and character values such as collaboration, communication, critical thinking, creativity, independence, integrity, and social responsibility. Using library research, this study systematically reviews policy documents and scholarly literature related to the Merdeka Curriculum, character education, and 21st-century competencies. The findings indicate that character development is most effective when schools integrate the dimensions of the Profile of Pancasila Students into intraculicular learning, implement the Project for Strengthening the Profile of Pancasila Students (P5), apply differentiated instruction and formative assessment, and foster a supportive school culture with strong parental and community partnerships. Despite these strengths, challenges remain, particularly regarding teacher readiness, consistency of school culture, administrative demands, and unequal resource support. The study recommends strengthening teacher capacity, aligning assessment with character indicators, and reinforcing a reflective and collaborative school ecosystem.Kata keyword: Merdeka Curriculum, Profile of Pancasila Students, character education 21st-century competencies.